Makna Persaudaraan Kristiani Dalam Ritus Tu Ju Pada Masyarakat Lisabheto, Flores Dalam Terang Injil Lukas 17:1-6 - Kua, Yoseph; Lina, Paskalis (Perspektif, 2025)
This article focuses on exploring one of the local wisdoms, namely the Tu Ju rite of the Lisabheto community, Wolowiro Village, Paga District, Sikka Regency, East Nusa Tenggara and reinterpreting it from a Christian perspective by taking the biblical basis of the Gospel of Luke, 17:1-6 as a reference. The problem of this research is how to translate the meaning of the Tu Ju ritual into the appreciation of fraternal life in the Lisabheto community? The research purposes is for the Lisabheto community to find correlation between the Tu Ju ritual and the enhancement of the Christian faith. The method used in this research is qualitative approach and field observation. This research data was obtained from direct interviews with key informants who understand the Tu Ju rite. The results of the research show that in the Tu Ju rite in the Lisabheto community there are Christian values, especially the value of brotherhood which is useful for a harmony and peaceful life together.